Post‐Perovskite Phase Transition in the Pyrolitic Lowermost Mantle: Implications for Ubiquitous Occurrence of Post‐Perovskite Above CMB. Issue 1 (4th January 2022) - Kuwayama, Yasuhiro; Hirose, Kei; Cobden, Laura; Kusakabe, Mayu; Tateno, Shigehiko; Ohishi, Yasuo
Abstract: We conducted in situ high‐pressure and ‐temperature X‐ray diffraction measurements of a pyrolitic mantle material up to 4480 K at 122–166 GPa in a laser‐heated diamond anvil cell. Results demonstrate that the phase transition between bridgmanite and post‐perovskite occurs in pyrolite within the lowermost mantle pressure range even at >4000 K. It suggests the ubiquitous occurrence of post‐perovskite above the core‐mantle boundary, which may be consistent with recent high‐quality seismology data that non‐observations of D" reflections are exceptions. Combining with earlier experiments performed at and below the normal lower‐mantle geotherm, our data show that the bridgmanite + post‐perovskite two‐phase region is ∼5 GPa thick and the d P /d T slope of the boundary is +6.5 ± 2.2 MPa/K, slightly smaller than previous theoretical calculations in MgSiO3 . The global presence of rheologically weak post‐perovskite at the bottom of the mantle has profound implications in seismology, geodynamics, and heat transfer from the core. Plain Language Summary: (Al, Fe)‐bearing MgSiO3 bridgmanite is a predominant mineral in the lower mantle. While bridgmanite with the MgSiO3 end‐member composition is known to undergo a phase transition to post‐perovskite at lowermost mantle pressures, the pressure, and thickness of the phase boundary in a typical mantle material (pyrolite) have been controversial. The present synchrotron X‐ray diffraction measurements of pyrolite performed up to 4480 K around the core‐mantle boundary (CMB) pressure show that the bridgmanite/post‐perovskite phase transition takes place within the lowermost mantle pressure range even under high temperatures of the CMB region. The bridgmanite + post‐perovskite two‐phase region is found to be about 90 km thick. These results suggest the global presence of post‐perovskite above the CMB, which is consistent with recent seismological observations of D" reflectors not only in the circum‐Pacific high velocity regions but also in many areas away from subduction zones. Post‐perovskite is rheologically weak, and its ubiquitous occurrence in the lowermost mantle has important seismological and geodynamical implications. The large positive d P /d T slope (+6.5 ± 2.2 MPa/K) of the boundary suggests that a phase transition from post‐perovskite to bridgmanite assists upwelling of plumes from hot regions above the CMB. Key Points: We conducted synchrotron X‐ray diffraction measurements of a pyrolitic mantle material up to 4480 K at 122–166 GPa in a laser‐heated diamond anvil cell Phase transition between bridgmanite and post‐perovskite occurs in pyrolite within the lowermost mantle pressure range even at >4000 K Ubiquitous occurrence of post‐perovskite above the core‐mantle boundary is consistent with recent high‐quality seismological observations of D" reflections